A review on the evaluation of horse coat color - Gaál, Zsófia Eszter; Posta, János (Acta Agraria Debreceniensis, 2026)
The coat color diversity of horses represents a classic example of the genetic and evolutionary effects of domestication. While wild equids exhibited limited pigmentation patterns, human-mediated selection has dramatically expanded phenotypic and genetic variation among domestic horses. This variation is influenced by multiple interacting loci, with some genes exerting pleiotropic effects on physiological and morphological traits. Modern molecular genetics has identified key loci controlling base colors (Agouti, Extension), dilution (D locus), greying (G locus), and patterned phenotypes including Tobiano and Overo, while also highlighting the increasing importance of additional white patterning mechanisms such as MITF and PAX3-associated Splashed White phenotypes and KIT gene complex variants (e.g., Sabino 1 and W1–W30 alleles). Furthermore, some coat color–associated mutations illustrate the fitness costs of selection, as seen in Overo Lethal White Syndrome (OLWS) and the association between the Silver dapple mutation and Multiple Congenital Ocular Anomalies (MCOA), emphasizing the pleiotropic and sometimes deleterious effects of pigmentation genes). Quantitative assessment using Lab* color metrics allows objective evaluation of coat pigmentation and facilitates comparisons across breeds, ages, and sexes. Phenotypic studies show that coat color does not directly correlate with performance or temperament but may affect thermoregulation, predator avoidance, disease susceptibility, and market value. Comparative research on other livestock species confirms that coat color is largely polygenic, heritable, and influenced by human selection. Integrating molecular and phenotypic analyses enhances our understanding of the evolutionary, genetic, and practical implications of coat color variation in horses. These insights support breeding decisions, breed identification, and the conservation of genetic diversity. Overall, the study of equine coat pigmentation provides a valuable model for investigating domestication, human-driven selection, and the genetic architecture of complex traits in livestock species.